TORRANO, Jaa. Mito e Imagens Míticas Editora Córrego: São Paulo, 2019, 154 p., ISBN: 978-85-7039-022-6. - Rachid, Rodolfo (CODEX - Revista de Estudos Clássicos, 2019)
Resenha de TORRANO, Jaa. Mito e Imagens Míticas Editora Córrego: São Paulo, 2019, 154 p., ISBN: 978-85-7039-022-6.